Thermal analysis of Cu-nanofluid based on sodium alginate and Al2O3 (aluminium oxide) with nanoparticles shapes effect under transverse magnetic field - Bibi, Sakeena; Majeed, Aaqib; Ahmad, Hijaz; Jamshed, Wasim; Eid, Mohamed R; Mohd Nasir, Nor Ain Azeany (SAGE Publications, 2025)
An innovative new generation of fluids for heat transmission is sodium alginate (SA) based nanofluid. Compared to normal fluids, these fluids’ thermophysical characteristics are quite traditional. This study examines the impact of nanoparticle form on Al2O3 (aluminium oxide)-based Cu-nanofluid and non-Newtonian viscoplastic sodium alginate (SA). The transverse magnetic field affects the sheet that is expanding or shrinking. Four distinct morphologies of disseminated nanoparticles cylinders, bricks, blades, and platelets within an assortment of sodium alginate (SA) with a Prandtl number Pr = 6.50 make up the not compulsory Cu-nanofluid and Al2O3. Non-linear PDEs are condensed into a structure of ODEs by proper similarity conversions, and these equations are solved analytically and numerically beside through boundary conditions (BC). Using the Runge–Kutta–Fehlberg (RKF) method, the altered equations’ numerical solutions have been achieved. Additionally, the use of the built-in differential equation solver Solve in MAPLE yields the analytical answers. The study investigates the effects of important parameters on the temperature and velocity fields of the nanofluid, such as the viscoplastic parameter and Eckert number. Our outcomes display that the temperature field upsurges for all shapes of nanoparticles with increasing Eckert number and viscoplastic parameter, with the highest thermal augmentation observed for platelets. Additionally, the nanoparticle shape has a significant impact on the velocity profiles; brick and cylindrical-shaped nanoparticles sustain higher flow velocities than platelets and blades. In order to improve heat transmission and flow control in nanofluid-based thermal systems, this study offers important insights into optimizing nanoparticle morphology. According to quantitative findings, platelets can experience a temperature increase of up to 25% when compared to cylindrical nanoparticles at higher Eckert numbers.